LIPID CONTROL IN PATIENTS AFTER MYOCARDIAL INFARCTION - AN EFFECTIVE TOOL FOR MANAGING CARDIOVASCULAR RISKS - O. L. Barbarash; V. V. Kashtalap (Атеротромбоз, 2017)
The review article highlights the views reflected in the recent clinical guidelines related to high-intensity statin treatment and non statin cholesterol lowering drugs in patients with very high cardiovascular risk after myocardial infarction and the purpose of therapy. The article tells about the approaches to controlling lipidogramic parameters after high-intensity statin therapy was prescribed and to the prescription of PCSK9 inhibitors (Alirocumab) after an acute coronary event. The report was compiled on the basis of the available materials from the national and foreign databases (e-Library, Library’s MEDLINE/PubMed database).